2023
DOI: 10.1039/d3qo01188g
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced stereo- and regiospecific sulfonylation of C–C multiple bonds exploiting the dual reactivity of sulfonium iodate(i) species

Aakanksha Gurawa,
Nitin Kumar,
Sudhir Kashyap

Abstract: Vinyl sulfones are privileged motifs for assembling prevalent biologically active molecules and represent “gateway functional groups” in medicinal chemistry and drug discovery. Augmented on our focus research toward bisfunctionalization of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 102 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…42 Zhang et al reported the violet (400 nm) light-induced synthesis of (E)-β-phenoxyvinylsulfones via an EDA complex-mediated radical reaction. 43 Using visible light, we, 44 Mutra et al, 45 and Gurawa et al 46 have recently shown that the photoinduced addition of RSO 2 I to internal alkynes in acetonitrile occurs with high yields and regio-and stereoselectivity. Such a reaction would represent in principle an ideal atom-saving process.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…42 Zhang et al reported the violet (400 nm) light-induced synthesis of (E)-β-phenoxyvinylsulfones via an EDA complex-mediated radical reaction. 43 Using visible light, we, 44 Mutra et al, 45 and Gurawa et al 46 have recently shown that the photoinduced addition of RSO 2 I to internal alkynes in acetonitrile occurs with high yields and regio-and stereoselectivity. Such a reaction would represent in principle an ideal atom-saving process.…”
Section: Introductionmentioning
confidence: 88%
“…Using visible light, we, 44 Mutra et al , 45 and Gurawa et al 46 have recently shown that the photoinduced addition of RSO 2 I to internal alkynes in acetonitrile occurs with high yields and regio- and stereoselectivity. Such a reaction would represent in principle an ideal atom-saving process.…”
Section: Introductionmentioning
confidence: 89%
“…Very recently, Kashyap and co-workers 26 presented the visible-light irradiated vicinal iodosulfonylation of alkynes 1 using sodium sulfinate salts 2 and sulfonium bis(acetoxy)iodate( i ) [Me 3 SI(OAc) 2 ] to synthesize the stereospecific ( E )-β-iodovinyl sulfones 3 (Scheme 9). Herein, Me 3 SI(OAc) 2 has dual reactivity as an iodine source as well as an oxidant.…”
Section: Synthesis Of β-Iodovinyl Sulfonesmentioning
confidence: 99%
“…In 2023, Kashyap's group proposed a photocatalytic (E)-stereospecific direct iodosulfonylation of alkynes using sulfonium iodate species (Scheme 21). [31] In this reaction, sulfonium bis-(acetoxy) iodate (I) [Me 3 SI(OAc) 2 ] (57) would generate the sulfonyl iodide (ArSO 2 -I) in the presence of sodium aryl sulfinate (ArSO 2 -Na, 46), followed by visible lightinduced homolysis of ArSO 2 -I, which leads to the regiospecific sulfonyl-iodination reaction with alkynes. In control experiments with styrene, the isolation of the β-iodosulfone confirmed a two-step sequential process of regioselective radical sulfonyliodination of an olefinic moiety under visible-light irradiation and subsequent β-elimination.…”
Section: Iodosulfonylationmentioning
confidence: 99%